Área de actividad, movimiento y organización social de Heteromys gaumeri Allen y Chapman, 1897 (Rodentia: Heteromyidae) en una Selva Mediana Subcaducifolia de Yucatán, México - Hernández Betancourt, Silvia F.; López Wilchis, R.; Cimé Pool, J. A.; Medina Peralta , S. (Instituto de Ecología, A.C., 2022)
The purpouse of this study was to examinate the dynamics of Home Range (HR) and the social behaviour of Heteromy sgaumeri in the  semidesiduos tropical forest of the south of Yucatan. We used the mark-and-release technique during four nights per month, from January 2000 to December 2001. Thirty four percent (n=174) of the total population was resident being 49% males and 51% females. The females had longer residence than the males (p<0.05). For both sexes home range (HR) and maximum distance moved (MDM) (p<0.05) were higher for adults than for yuongs, seasonality did not affect them (p>0.05). Reproductive females were territorial and had lower HR and MDM than no reproductive females (p<0.05). Males and females had similar HR (p>0.05), males did not show territoriality. The total overlapping of HR was low for both sexes and both reproductive conditions. In the rain season reproductive males had a higher overlapping percentage than that of reproductive females (p<0.05). The results suggest that H. gaumeri is a social species with a promiscuous mate system.